Early Aortic Valve Replacement of Asymptomatic Severe Aortic Stenosis: A Meta‐Analysis of Randomized Controlled Trials - Qingchun Song; Ruilin Liu; Kai Yang; Xiaokang Tu; Haoyu Tan; Chengming Fan; Xiaoxiao Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Asymptomatic severe aortic stenosis may lead to the progression to both symptoms and adverse outcomes if left untreated. The appropriate timing of intervention for these patients remains controversial, and any decision requires careful assessment. Methods We searched PubMed, Web of Science, EMBASE, and Cochrane Library for randomized controlled trials comparing early aortic valve replacement with conservative management in asymptomatic patients with severe aortic stenosis until December 2024. The primary efficacy outcome was a composite of all‐cause mortality, hospitalization for cardiovascular causes, stroke, and myocardial infarction. We expressed outcome data as risk ratios (RRs) with 95% CIs. Results We included 4 randomized controlled trials involving 1427 patients. Early aortic valve replacement significantly reduced the incidence of the composite outcome when compared with conservative management (29.2% versus 53.7%; RR, 0.56 [95% CI, 0.49–0.64]; I2=60%). Significant reductions were also detected in all‐cause mortality (10.0% versus 13.7%; RR, 0.74 [95% CI, 0.55–0.99]; I2=58%), hospitalization for cardiovascular causes (14.6% versus 32.5%; RR, 0.48 [95% CI, 0.39–0.58]; I2=26%), and stroke (4.5% versus 7.2% RR, 0.62 [95% CI, 0.40–0.95]; I2=0%). No significant difference was observed in cardiac‐specific mortality (8.3% versus 16% RR, 0.68 [95% CI, 0.40–1.16]; I2=65%) and myocardial infarction (0.6% versus 4.6%; RR, 0.21 [95% CI, 0.04–1.19]; I2=0%). Conclusions Our meta‐analysis of randomized controlled trials showed that among patients with asymptomatic severe aortic stenosis, a strategy of early aortic valve interventions was superior to conservative treatments in reducing the primary composite outcome of all‐cause mortality, hospitalization for cardiovascular causes, stroke, and myocardial infarction. However, significant differences in the rates of cardiac‐specific mortality were not apparent.